2002
DOI: 10.1002/fut.10008.abs
|View full text |Cite
|
Sign up to set email alerts
|

Mean reversion in stock index futures markets: A nonlinear analysis

Abstract: Several stylized theoretical models of futures basis behavior under nonzero transactions costs predict nonlinear mean reversion of the futures basis towards its equilibrium value. Nonlinearly mean-reverting models are employed to characterize the basis of the S&P 500 and the FTSE 100 indices over the post-1987 crash period, capturing empirically these theoretical predictions and examining the view that the degree of mean reversion in the basis is a function of the size of the deviation from equilibrium. The es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This de-mean strategy was also applied in He and Sandberg (2005). Empirical examples in Venetis et al (2009) and Monoyios and Sarno (2002) support the assumption is satisfied in practice.…”
Section: A New Approach Of Unit Root Test For a K-estar(p) Modelmentioning
confidence: 73%
See 1 more Smart Citation
“…This de-mean strategy was also applied in He and Sandberg (2005). Empirical examples in Venetis et al (2009) and Monoyios and Sarno (2002) support the assumption is satisfied in practice.…”
Section: A New Approach Of Unit Root Test For a K-estar(p) Modelmentioning
confidence: 73%
“…Terasvirta and Elliasson (2001), and Sarno et al (2002) used ESTAR models to analyse deviations from optimal money holding. Monoyios and Sarno (2002) found that symmetric deviations from arbitrage processes such as stock index futures follow ESTAR models. In economics and finance theories such as real exchange rate, PPP, and arbitrage processes, ESTAR models can be characterised by a unit root behaviour in the inner regime, but for large deviations, the process is mean reverting.…”
Section: Introductionmentioning
confidence: 99%